Investigation of photophysicochemical properties of peripheral tetra-substituted Zn(II) and Mg(II) phthalocyanine compounds containing thiol group - Guney, Gunseli; Penlik, Yunus; Avciata, Oguzhan; Gorduk, Semih (ELSEVIER, 2025)
Phthalocyanines having significant benefits are photosensitizers for photodynamic treatment (PDT) and are at the forefront of PDT applications because of their strong absorption, high photostability, formation of reactive oxygen, selective accumulation, and suitableness for chemical modification and new discoveries necessitate the exploration of additional compounds. This work presents the synthesis, characterization, photochemical, photophysical, and aggregation properties of novel peripheral tetra-substituted Zn(II) (THL-ZnPc) and Mg(II) (THL-MgPc) phthalocyanine derivatives of 4((4,5-diphenyloxazol-2-yl)thio)phthalonitrile (THL-Pht) as a photosensitizer for PDT applications. Conventional methods were applied for the synthesis of Pc compounds, and spectroscopy techniques such as Ultraviolet and Visible light (UV-Vis), Fourier transform infrared (FT-IR), Nuclear magnetic resonance (NMR), and Matrixassisted laser desorption/ionization mass (MALDI-TOF MS) spectroscopy were used for characterization. Dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO) solvents were used in order to examine the aggregation behaviors of THL-functionalized phthalocyanines. The photochemical and photophysical characteristics of these phthalocyanines were first studied in DMSO and DMF for the purpose to assess their potential for PDT. The singlet oxygen quantum yield (Phi Delta) values of the compounds were found to be between 0.53-0.68 for THL-ZnPc and 0.41-0.46 for THL-MgPc in different solvents. In conclusion, these phthalocyanines show potential as photosensitizers for PDT investigations based on their singlet oxygen, photodegradation, fluorescence, and aggregation properties.
Keywords: Phthalocyanine; Zinc(II); Magnesium(II); Thiol; Photodynamic therapy; Singlet oxygen; METAL-FREE; PHOTOCHEMICAL PROPERTIES; ZINC II; DERIVATIVES; Chemistry